Desenvolvimento e Caracterização de Nanopartículas Políméricas Contendo Ácido Ferúlico - Heep, Graciela Leila (2019)
Ferulic acid (FA) is a phenolic compound belonging to the class of hydroxycinnamic acids. For oral administration has limitations in its therapeutic efficacy. It has low water solubility, reduced ability to penetrate biological membranes and low cell absorption. The use of nanocarrier systems can be an alternative to improve the physicochemical and bioavailability aspects. Two carrier systems with PA were developed, one with casein and one with zein-casein-lysine. Casein nanoparticles were obtained by the desolvation method, while those of zein-casein-lysine were obtained by the liquid-liquid dispersion method. The formulations developed had their mean diameter (DM), polydispersion index (IPD) and Zeta potential determined by Dynamic Light Scattering measurements. For casein nanoparticles, 170 nm DM and 0.26 IPD and Zeta-23 mV potential were obtained, while for zein-casein-lysine system, 200 nm DM and 0.17 IPD and Zeta potential were obtained. -26 mV. The quantification of the FA was performed by high performance liquid chromatography (HPLC) with diode array detector (DAD) obtaining an encapsulation efficiency (EE) of 26% for casein particles and 23% for zein-system. casein-lysine. The obtained particles were characterized by Fourrier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and field emission scanning electron microscopy (SEM-FEG). Photomicrographs confirmed the size and spherical morphology of the particles. The FT-IR did not indicate the formation of new functional groups, while in the diffractograms there were no characteristic diffraction peaks of FA crystal structure, indicating that it was incorporated into the nanostructured system, suggesting the amorphization of the compound. Zein-casein-lysine nanoparticles were also evaluated for cytotoxicity against Caco-2 and HT29-MTX cells, two intestinal strains, to verify their biocompatibility and safety. In addition, Caco-2 monoculture intestinal permeability and Caco-2 / HT29-MTX co-culture assays proved satisfactory for this FA carrier system.